Die Shoah im Spiegel öffentlicher Konflikte in Polen Zwischen Opfermythos und Schuldfrage (1985-2001) - Kowitz-Harms, Stephanie (Europäisch-jüdische Studien - Beiträge, 2013)
Since the mid-1980s, public discourse in Poland has repeatedly focussed on the issue of how to deal with the National Socialists` destruction of the Jews. This has raised accusations that the Polish people bore an element of moral or active guilt which, however, conflict with the country`s long-established perception of itself as a community of heroes and victims. The author examines the question of how Polish society is handling this contradiction.